Analisis Efektivitas Mesin Injection 2500 Ton di Bagian Produksi PT.XYZ Menggunakan Metode Overall Equipment Effectiveness - Sri Widiyanti Putri; Ade Momon; Wahyudin Wahyudin; Salim Fikri (Fakultas Teknik, 2022)
PT. XYZ is an industrial company that focuses on manufacturing automotive components. The company also has many branches in various countries such as in the USA, India, China, Japan, Vietnam, Thailand and Malaysia. The machine used in this company is an injection molding machine. PT. XYZ focuses its company on manufacturing car interior components. Many activities are carried out in it such as the injection process, painting to assembly. Data for the injection engine of 2500 TON experienced downtime or damage for the last three months (January-March 2022) which was 10,055 minutes, where the highest injection engine downtime data occurred in January 2022 of 3685 minutes. It is necessary to evaluate the injection machine to be able to determine the effectiveness of the injection machine using the Overall Equipment Effectiveness (OEE) method by looking for values from availability, performance to quality. Based on the results obtained in these three months, it does not meet international standards at an OEE score of 85%.